Radiographic parameters of the normal ankle syndesmosis: Comparison between hindfoot alignment view and anteroposterior view - Jaehyung Lee; Ho Seong Lee; Ji Wan Kim; Bum-Sik Lee; Youngrak Choi (Journal of International Medical Research, 2022)
Objective To compare the parameters associated with the normal ankle syndesmosis between the hindfoot alignment view (HAV) and anteroposterior (AP) view and determine which view is more accurate for comparing the left and right ankles. Methods This study involved 61 subjects without syndesmosis injury who had radiographs of both ankles. The tibiofibular clear space (TFCS), tibiofibular overlap (TFO), and medial clear space (MCS) were measured in each view. Intraclass correlation coefficients were used to assess the agreement between the two ankles. Difference ratios for the measured parameters between the ankles were also compared. Results The agreement for TFCS showed wide disparity between the two ankles (AP view, 0.576; HAV, 0.858). The highest degree of agreement was seen for TFO (AP view, 0.733; HAV, 0.926). The agreement for MCS was low in both groups. The mean difference ratio for TFCS was also lower in the HAV group (9.9%) than in the AP view group (16.4%); a similar result was observed for TFO (16.4% vs. 25.8%). Conclusions For evaluation of the syndesmosis, use of the HAV showed increased accuracy and few measurement errors when comparing the left and right ankles relative to use of the AP view.